Symptoms of psychological burden on health care providers regarding Covid-19 - AL MERAB, MONEERAH MOHAMMAD; HAMZA, Ahmed M.; ELSAYED , H.A.; AHMED MOHAMED , Z. (Utopía y Praxis Latinoamericana, 2021)
ABSTRACTThe COVID-19 pandemic has affected an increasing number of healthcare providers. However, they face vast physical and psychological challenges. Therefore, we assessed healthcare providers’ symptoms of psychological burden concerning their response to the COVID-19 pandemic. A sample of healthcare providers completed the Depression Anxiety Stress Scale online. Analyses were performed on participants ’psychological burden symptoms since the COVID-19 outbreak. COVID-19 caused a relatively significant level of psychological burden among healthcare providers. Analyses showed that academic qualification was the main factor affecting this burden. Applying the online program could reduce the psychological burden on healthcare providers. RESUMENLa pandemia de COVID-19 ha afectado a un número creciente de proveedores de atención médica. sin embargo, enfrentan grandes desafíos físicos y psicológicos. Por lo tanto, evaluamos los síntomas de carga psicológica de los proveedores de atención médica con respecto a su respuesta a la pandemia de COVID-19. Una muestra de proveedores de atención médica completó la Escala de estrés, ansiedad y depresión en línea. Se realizaron análisis de los síntomas de carga psicológica de los participantes desde el brote de COVID-19 que causó un nivel relativamente significativo de carga psicológica entre los proveedores de atención médica. Los análisis mostraron que la calificación académica fue el principal factor que incidió en esta carga. La aplicación del programa en línea podría reducir la carga psicológica en los proveedores de atención médica.